Initial Engineering Studies of Battery Capacity Prediction Power of "Electric Ship of FTK UNSADA" Container Concept from Jakarta to Ibu Kota Nusantara - Buwono, Ayom; Muslim, Muswar; Irvana, Rizky; Manullang, Shanty; Dariansyah, Ricky; Partahi Oloan, Aldyn Clinton (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
Addressing global issues like climate change requires transformative solutions, and the shipping industry is no exception. Moving towards emission-free ship design has become a critical need, offering a chance to significantly reduce greenhouse gas emissions from maritime transport. In 2018, the International Maritime Organization (IMO) adopted a bold strategy to cut these emissions by at least 50% by 2050. Embracing renewable energy sources like batteries, wind, solar, and hydrogen fuel cells is key to achieving this ambitious goal. While electric ships powered by batteries are pioneering the way, meeting the IMO's target will necessitate radical changes in future ship design. Here, Indonesia holds a unique advantage, the legacy of the Sriwijaya Empire renowned for its mastery of wind-powered ships, resonates with this emerging era of green shipping. Abundant sunshine, strong wind potential, and growing expertise in maritime engineering position Indonesia to become a leader in the development and deployment of sustainable ship designs. Harnessing these historical and contemporary strengths, Indonesia can play a pivotal role in revolutionizing the shipping industry. By fostering collaboration between policy makers, researchers, and shipbuilders, Indonesia can spearhead the transition to a future where cargo ships navigate the oceans propelled by the clean power of renewable energy, leaving behind a legacy of environmental stewardship and economic prosperity. This paper estimates the energy consumption and power needs of Container ships on short inter-island routes in Indonesia, with a particular focus on the potential application of batteries in such scenarios. The initial design utilizes similar vessel data collected from various locations around the world. Our findings indicate that a container ship operating on the Jakarta-Semarang route would require batteries with a capacity of 15.25 MWh, Semarang to Surabaya route would require 12.20 MWh batteries, from Surabaya-Tanjung Benoa Bali route required 15.25 MWh, from Tanjung Benoa Bali to Ujung Pandang route require 21.35 MWh batteries, all with a capacity of 1.5 MWh each and from Ujung pandang – Ibu Kota Nusantara require 18.3 MWh. These calculations assume normal sea and weather conditions and a design speed of 10 knots. Implementing battery-powered Containers on these routes reduces the CO2 emission into the air as long as the ship route operates.